Síntese e caracterização de novos complexos mistos contendo ligantes nitrogenados e pseudo-haletos e o estudo das suas potenciais aplicações - Fogos, Wagner Fernandes (2015)
The development of new species containing pyrazolyl ligands have over the years been increasing, much of the interest in binders of this class consists of its diverse coordination modes, which allow a wide structural diversity. This work invested in the synthesis and characterization of complexes of Cu (II) and Pd (II) with the following pyrazolyl ligands:, 1-carbamoyl-3,5-dimethylpyrazole and 1-thiocarbamoyl-3,5-dimethylpyrazole, and pseudohaleto thiocyanate. The synthesis routes were carried out at room temperature and methanol or acetone as solvent to give the compounds [Pd(Cdmpz) 2] (1), [Pd (SCN)2Cdmpz] (2), [Cu(Cdmpz)2Cl2] (3) [Pd(Tdmpz)Cl2] (4) [Pd(SCN)2(Tdmpz)] (5) and [Cu (Tdmpz)Cl2] (6) which the compounds 2, 3, 5 and 6 are not reported in the literature. It was observed in the IR spectra of the tendency of pyrazolyl ligands, applied here, a strong tendency to coordinate in bidentate mode, where the coordination points are strongly influenced by the applied solvent. In the study the thermal behavior of the pyrazole compounds of palladium (II) and copper (II) it was found that the compounds of Pd with linkers 1-carbamoyl-3,5-dimethylpyrazole and 1-thiocarbamoyl-3,5-dimethylpyrazole present higher thermal stability than the compounds of copper. The thermal stability of the compounds presented follows the following order: [Pd (Cdmpz) 2] (1 )> [Pd(SCN) 2Cdmpz] (2) > [Pd (Tdmpz)Cl2] (4) > [Pd(SCN)2Tdmpz] (5) > [Cu (Tdmpz)Cl2] (6)> [Cu (Cdmpz) 2Cl2] (3).